Skill mismatch and work–life conflict: the mediating role of job satisfaction. Issue 2 (17th February 2019) - Shevchuk, Andrey; Strebkov, Denis; Davis, Shannon N.
ABSTRACT: Previous research examining skill mismatch in the labour market has ignored potential implications for workers outside of the work environment. We argue that the psychological strain that the discrepancy between worker's skills and job requirements wields on workers spills over into the non-work sphere, increasing work–life conflict. This study explores the consequence of skill mismatch for work–family life and various dimensions of job satisfaction. Using the 2011 British Workplace Employment Relations Survey (WERS), we find that both over- and underskilled workers reported lower satisfaction with achievement and autonomy, opportunity for development, and pay and security. Results also suggest that not only does skill mismatch have a negative influence on work–life conflict but that this association is completely mediated through job satisfaction. Given this better understanding of the complex ways that skill mismatch in employment shapes non-work life, implications for employees and firms are discussed.